Pemberdayaan Keluarga dalam Merawat Anak Balita dengan Pneumonia Pasca Hospitalisasi - Dhea Natashia; Anita Apriliawati; Dewi Purnamawati; Emmy Putri Wahyuni; Tri Imrotun; Yuniarsih Yuniarsih; Nyimas Heny Purwati (Sagamedia Indo Press, 2023)
Background: Pneumonia is an acute respiratory infection that attacks the lungs. Pneumonia causes symptoms of difficulty breathing which if left untreated will lead to death. Families with problems with family members who experience illness or disease often make the family unable to meet health care needs or experience powerlessness which worsens the health condition of family members who experience health problems. Nursing intervention is needed to overcome the problem of family powerlessness. Objectives: This community service aims to increase mothers' knowledge and perceptions of caring for toddlers with pneumonia after being hospitalized at Pasar Rebo Hospital. Methods: The method used consists of identifying problems and needs, assessing problems, formulating plans, providing health education, and monitoring the ability of mothers to care for toddlers with pneumonia after being hospitalized. This community service was carried out for four months from June to September 2022. The health education activity was carried out for one day in the children's care room at Pasar Rebo Hospital. The target of this community service activity is mothers who have toddlers with pneumonia who are treated at Pasar Rebo Hospital as many as 10 people. Results: The results of the evaluation show that the average value of knowledge is post-test> pre-test and the average value of attitude is post-test> pre-test. Conclusion: There is an increase in the knowledge and attitude of mothers in caring for children under five with pneumonia after hospitalization. Health education needs to be carried out on an ongoing basis for mothers who have children under five with post-hospitalization pneumonia so they can carry out optimal care and prevent repeated treatments.